Exploring Character Building in Junior High School: Literature Review from Scopus Database - Nurhayati, Enung; Suryana, Asep; Rahyasih, Yayah (BRILIANT: Jurnal Riset dan Konseptual, 2025)
The purpose of this study is to investigate how character education is implemented at the junior high school (SMP) level by conducting a thorough literature review using the Scopus database. The approach is a review of the literature that involves examining academic papers over the past ten years that are relevant to character education in junior high schools. The findings of the study demonstrate the significance of character education in forming junior high school students' moral principles and personalities. The inclusion of character values in the curriculum, mentorship programs, extracurricular activities, and parental involvement are a few of the successful tactics that have been found. The primary obstacles encountered include variations in student backgrounds, scarce resources, and inconsistent implementation. This study also shows how crucial it is for communities, families, and schools to work together in a holistic manner in order for character education to be successful. In conclusion, a thorough and long-lasting strategy is needed for character education in junior high schools. For the purpose of creating successful character education programs at the junior high school level, researchers, educators, and policymakers can benefit greatly from the insights this study offers.